School Financial Management in Improving the Quality of Facilities and Infrastructure: A Case Study at Madrasah Tsanawiyah - Mulyadi Mulyadi; Dewi Cahyani; Nurul Azizah; Lulu Awaliyah; Syibromilisi Syibromilisi (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
This research investigates the involvement of financial management in improving sustainable infrastructure quality of educational institutions in MTs Negeri 11 Cirebon. Qualitative case study research design was used whereby 14 informants consisting of the madrasah principal, treasurer, chairman of the committee, teachers, administrative staff, and students were involved. Data collection methods included interviews, observations, and documentation. Based on the results of this research, the process of financial management was conducted using participatory management by implementing the plan of RKAM/RKAS and was funded from two primary sources namely BOS/DIPA funds and community contribution The budget allocation emphasized the building of classrooms, maintenance of the infrastructure of education institution, and provision of learning facility. Nevertheless, problems were also encountered by the institution such as lack of BOS funding flexibility, delays in disbursements of fund, and the legality of the land still unresolved. The innovation of this research is in terms of integrating the discussion about financial management and sustainability of the infrastructure quality of educational institutions. From the result, it is evident that the sustainability of the infrastructure quality of education institution required not only fundings but also participatory governance, adaptive management, accountability, and multi-source funding approaches.